2012
DOI: 10.1080/14739879.2012.11494151
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the learning experiences of full-time (FT) trainees and less than full-time (LTFT) trainees in general practice

Abstract: The paper describes a small-scale enquiry amongst GP specialty trainees that aimed to identify the educational experiences and perceptions of trainees training less than full-time (LTFT). The study found several significant challenges facing these trainees, as well as positive aspects of training LTFT. The work has led to the development of a peer-mentoring scheme in Dorset and monthly meetings of an LTFT group to improve support for these trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Some parallels are also evident with respect to a study that compared experience with specialist training between full-time and part-time employees. Satisfaction of part-time employees was lower ( 27 ). A “suitable place for rest” also proved to be an important factor for higher FMT satisfaction with working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some parallels are also evident with respect to a study that compared experience with specialist training between full-time and part-time employees. Satisfaction of part-time employees was lower ( 27 ). A “suitable place for rest” also proved to be an important factor for higher FMT satisfaction with working conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the small number of who were successful in securing flexible training positions often reported prejudice, being undermined or that their professional opinion was not valued by the rest of the team (15,18,20,21). Private time for study, examination preparation or opportunity to attend professional meetings/ conferences can be reduced or completely foregone by LTFT doctors (21). Interestingly, the Royal College of Physicians Report (17) showed that in medical specialties, working LTFT did not adversely affect the chance of being appointed to a substantive consultant post.…”
Section: Training Pathwaysmentioning
confidence: 99%
“…Another study found that less than full-time (LTFT) trainees were often less integrated into their teams and felt more remote than full-time (FT) trainees in UK general practice. 13 Interviews with UK hospital consultants revealed a resistance, generally, to flexible working and part-time work. 14 The authors point out that, because most part-time doctors are women, they are affected more than men.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%